ORIGIN OF THE DOMESTICATED HUSBANDRY SPECIES AND MOLECULAR-BASES OF FRUIT FORM AND SIZE CHANGES THROUGHOUT THE DOMESTICATION, TAKING TOMATO AS AN EXAMPLE - LINKIN, DR.DANG LEW; ARNOLD, SCHANONCIFF (International Journal of Multidisciplinary Research and Studies, 2021)
The domestication of crop plants is the foundation of modern agriculture, which brings forth desirable changes in cultivated species that distinguish them from their wild relatives. This resulted in the origin of crop species at glorious geographical locations coinciding with the transition of human societies from hunter-gather to agricultural civilizations. Fruit size and shape are very important traits for the horticulture industry, as well as for studying the domestication of the horticultural species. In this review, we have summarized the origin of some widely-grown horticultural crops and also the molecular bases of the fruit size and shape changes of the horticultural crops during the domestication, taking tomato as an example.